Switchable colloids, thin-films and interphases based on metal complexes with non-innocent ligands: the case of valence tautomerism and their applications. Issue 25 (20th May 2016) - Vázquez-Mera, N. A.; Novio, F.; Roscini, C.; Bellacanzone, Ch.; Guardingo, M.; Hernando, J.; Ruiz-Molina, D.
Abstract : Nanostructuration of valence tautomeric systems as colloids, thin-films and interphases, and their applications. Abstract : Successful nanostructuration approaches developed in the last few years have allowed the preparation of robust valence tautomeric (VT) switchable (micro-/nano-) structures of a variety of dimensions and morphologies. These results are expected to definitely foster the implementation of these materials on hybrid molecular electronic devices but also endorse new applications in other different fields such as sensing, drug delivery or water remediation, among others.